Budget and fate of sedimentary trace metals in the Eastern China marginal seas. (15th December 2020) - Sun, Xueshi; Fan, Dejiang; Liu, Ming; Liao, Huijie; Zheng, Shiwen; Tian, Yuan
Highlights: Budgets and depositional fate of trace metals in the ECMS were investigated. ECMS plays an important role in the global TM cycle. Coastal erosion input exerts a significant impact on TM budgets. Natural processes control the distributions of Pb, Zn, Cu, and Cr. Sedimentary As is primarily affected by anthropogenic activities. Abstract: To achieve a better understanding of global biogeochemical cycle and budget of trace metals (TM) in the world's ocean, a comprehensive study of the level, fate and burial flux of TM in surface sediment from the Eastern China Marginal Seas (ECMS) was conducted. The results indicated that Pb, Zn, Cu, and Cr were highly concentrated in mud deposits and primarily controlled by the natural processes of sediment composition and regional hydrodynamics, whereas As had a close association with Mn and was mainly derived from anthropogenic activity. The sediment mass inventories of Pb, Zn, Cu, Cr, and As in the ECMS (~220, 780 km 2 ) were estimated to be 28, 324, 92, 192, 23, 434, 94, 560 and 11, 968 t/yr, respectively. A mass budget model revealed that riverine runoff, coastal erosion input and atmospheric deposition (dry and wet) constituted 62–76%, 15–37% and 2–9% of the total Pb, Zn and Cr influxes, respectively, while more than 4, 690 t of Cu annually outflowed to the open seas to balance the budget. More importantly, we found that the sum of the estimates of these contributions tended to fall short of the calculated depositional fluxes of As, implying that anthropogenic activities probably have altered the natural geochemical cycle of As. Our results suggest that the ECMS constitutes a major final repository of TM at the Asia scale; however, the burial fluxes of trace metals are expected to decrease due to enhanced environmental investments by the Chinese government and decreased suspended particulate TM loads from the Chinese major rivers. Graphical abstract: Image, graphical abstract